Room-temperature application of VO2 microstructures on rigid and flexible substrates based on synthesis of crystalline VO2 solution. Issue 6 (9th September 2020) - Taha, Mohammad; Mayes, Edwin L. H.; Field, Matthew R.; Sun, Miao; Singh, Mandeep; Zou, Wenyue
Abstract : An innovative method that enables the deployment of thermochromic VO2 microstructures at room temperature for infrared (IR) modulation. Abstract : The insulator-to-metal transition (IMT) in vanadium dioxide (VO2 ) offers temperature-dependent infrared wavelength attenuation, rendering it a great contender for bolometers, optoelectronics, memory devices, smart-windows adaptive thermal camouflage applications. However, the required high temperature processing (up to 600 °C) of VO2 inhibits its widespread utilization, particularly in applications with low fabrication temperature limits – such as devices on flexible polymer substrates. This study provides a new method that relies on van der Waals substrates with inert basal planes and hydrophilic surfaces to overcome the hurdle of high processing temperatures. Using this method, highly-oriented, optically active crystalline VO2 was deposited on both glass and flexible polyethylene terephthalate (PET) substrates. We observe VO2 crystals during IMT using transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and report >60% change in transmission on both glass and flexible PET, as well as demonstrating IR modulation.